Molecular Insights and Therapeutic Targets in Amyotrophic Lateral Sclerosis - Al-Chalabi, Ammar; Tripathi, Vineeta B. (CNS & Neurological Disorders - Drug Targets, 2008)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of motor neurons resulting in progressive paralysis and respiratory failure. About 1 in every 400 people dies of ALS, usually within 3 to 5 years of symptom onset. The lack of effective therapy means that although the incidence is comparable to that of multiple sclerosis, the prevalence is low. The causes of ALS are largely unknown, but the only disease-modifying therapy, riluzole, was designed based on one hypothesis of disease causation, the excitotoxic hypothesis. In this paper we will review current ideas about the causes of ALS and the therapeutic opportunities they suggest.